Daya hambat xylitol dan nistation terhadap pertumbuhan Candida albicans (in vitro) (Inhibition effect of xylitol and nistatin combination on Candida albicans growth (in vitro)) - Sarah Kartimah Djajusman; Udijanto Tedjosasongko; Irmawati Irmawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: The growth of Candida albicans can be controlled by using antifungal such as nystatin. These days we found that using antifungal is not enough to control Candida albicans, we also have to control the intake of sugar by using xylitol. Purpose: Purpose of the study was to determine the optimal inhibitory concentration of xylitol-nystatin in the Candida albicans growth. Methods: This was an in-vitro study using an antimicrobial test of serial dilution with xylitol-nystatin and sucrose–nystatin consentration of 1%, 3%, 5%, 7%, 9%, and 10%.Growth inhibition of C. albicans was determined by the inhibition zone of xylitol + nystatin on C. albicans culture media (in vitro) Results: The result of study was the inhibitory consentration of xylitol-nystatin to inhibit Candida albicans growth was 3%-10%. Conclusion: The study showed that combination of xylitol and nystation could inhibit the growth of Candida albicans.Latar belakang: Pertumbuhan Candida albicans dapat dikontrol dengan menggunakan antijamur seperti nistatin. Penggunakan antijamur saja tidak cukup untuk mengontrol Candida albicans, namun perlu pula mengontrol asupan gula dengan menggunakan xylitol. Tujuan: Tujuan dari penelitian ini adalah untuk menentukan konsentrasi hambat optimal xylitol-nistatin dalam pertumbuhan Candida albicans. Metode: Penelitian ini merupakan penelitian in vitro menggunakan uji antimikroba pengenceran serial dengan xylitol-nistatin dan nystatin-sukrosa konsentrasi 1%, 3 %, 5 %, 7%, 9%, dan 10%. Daya hambat pertumbuhan C. albicans diukur dari zona hambat xylitol + nistatin pada media kultur C. albicans (in vitro) Hasil: Konsentrasi penghambatan xylitol-nistatin untuk menghambat pertumbuhan Candida albicans adalah 3-10%. Simpulan: Hasil penelitian menunjukkan bahwa kombinasi xylitol dan nystation bisa menghambat pertumbuhan Candida albicans.